The Silent Mineral: Structural Complexity and Industrial Utility of Natural Kaolin - Sandeep Rai (International Journal of Crystalline Materials, 2025)
Kaolin, a naturally occurring aluminosilicate clay predominantly comprising the mineral kaolinite (Al₂Si₂O₅(OH)₄), exhibits a 1:1 layered silicate structure that imparts distinctive physicochemical properties suitable for extensive industrial utilization. Deposits of kaolin are broadly classified into primary (residual) and secondary (sedimentary) categories, each defined by their geological origin and mineralogical features. The industrial processing of kaolin encompasses stages such as raw material extraction, beneficiation, and purification, aiming to optimize parameters including brightness, granulometry, and impurity removal to conform to specific application standards. Functionally, kaolin is integral to various sectors: it is employed in papermaking as a filler and surface pigment to enhance print characteristics; in ceramic manufacturing, it contributes to workability and mechanical integrity of fired bodies; and in paint formulations, it serves as an extender and rheological control agent. Beyond conventional domains, kaolin's role has expanded to encompass catalytic applications, notably in biodiesel synthesis, and environmental technologies, particularly in adsorption-based pollutant remediation. Attributes such as chemical inertness, low cation exchange capacity, fine particle morphology, and non-abrasive texture render it suitable for high-performance and sustainable solutions. With global production volumes approximating 45 million tonnes annually, kaolin remains a critical industrial mineral. This review provides a comprehensive overview of kaolin’s structure, chemical behavior, processing strategies, and multifaceted applications, emphasizing its emerging relevance in environmental, medical, and advanced material sectors.
Keywords: China clay; Kaolinite; kaolin; raw kaolin; refractory